Folic acid determination using electrochemical sensors - Leila Mirmoghtadaie; Nahal Shamaeizadeh; Nooshin Mirzanasiri (International Journal of Preventive Medicine, 2015)
Folic acid (FA) is a water soluble vitamin that exists in many natural species. The lack of FA causes some deficiencies in the human body, so finding a simple and sensitive method for determining the FA is important. One of the modern techniques which overcome the disadvantages of conventional determination methods is the sensors. Possibility of miniaturization, the development of microfabricated electrochemical (EC) sensors has resulted in high sensitivity, portability, improved performance and spatial resolution, low power consumption, and the opportunity for integration with other technologies made Micro-Electrical-Mechanical Systems-based EC sensors suitable to identify low concentration analytes and microorganisms in a variety of mediums.